2017
DOI: 10.1186/s13054-017-1710-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat and moisture exchangers (HMEs) and heated humidifiers (HHs) in adult critically ill patients: a systematic review, meta-analysis and meta-regression of randomized controlled trials

Abstract: BackgroundThe aims of this systematic review and meta-analysis of randomized controlled trials are to evaluate the effects of active heated humidifiers (HHs) and moisture exchangers (HMEs) in preventing artificial airway occlusion and pneumonia, and on mortality in adult critically ill patients. In addition, we planned to perform a meta-regression analysis to evaluate the relationship between the incidence of artificial airway occlusion, pneumonia and mortality and clinical features of adult critically ill pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 77 publications
0
20
1
1
Order By: Relevance
“…Our protocol led to an increase in the proportion of patients showing ∆P ≤ 14 cmH 2 O from 39 to 89%, thus suggesting a possible clinical benefit by this approach. Although V T and ∆P reductions are among the most important modifiable factors capable of improving survival during ARDS [47], the use of HH was not associated with improved clinical outcome in wide unselected cohorts of mechanically ventilated patients [48]. In previous studies, however, the use of HH was not systematically accompanied by V T reduction as it is in our protocol, so that any possible benefit could have been underestimated.…”
Section: Discussioncontrasting
confidence: 55%
“…Our protocol led to an increase in the proportion of patients showing ∆P ≤ 14 cmH 2 O from 39 to 89%, thus suggesting a possible clinical benefit by this approach. Although V T and ∆P reductions are among the most important modifiable factors capable of improving survival during ARDS [47], the use of HH was not associated with improved clinical outcome in wide unselected cohorts of mechanically ventilated patients [48]. In previous studies, however, the use of HH was not systematically accompanied by V T reduction as it is in our protocol, so that any possible benefit could have been underestimated.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, there must be a 24 h humidification strategy in place for all patients with a tracheostomy. Mechanical ventilation ideally requires humidification and this can be achieved through different methods with no distinct advantages of one against the other [31]. Concerns were raised early on in the UK's pandemic experience regarding the potential for "wet" circuits to generate virus-laden aerosols at times of disconnection.…”
Section: Humidificationmentioning
confidence: 99%
“…Following data extraction, we included 34 studies (36 citations) and excluded 29 (29 citations). Two studies (76 participants) are awaiting classification, one by Nadir Oziş 2009 until data can be obtained from authors and one by Oguz 2013 identified from a recently published review (Vargas 2017).…”
Section: 'Summary Of Findings' Table and Gradementioning
confidence: 99%